2011
DOI: 10.1002/jsfa.4536
|View full text |Cite
|
Sign up to set email alerts
|

Extruded aquafeeds containing distillers dried grains with solubles: effects on extrudate properties and processing behaviour

Abstract: Extrudates from all treatments exhibited high durability and floatability, and less energy was required to produce extrudates when DDGS was used compared with soybean meal-based diets. The aquaculture industry can use this information to develop high-quality feeds at low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Expansion is mainly governed by the sudden decrease in pressure attheat the die section, which results in water phase transition and formation of air cells in the extrudates (Alves et al, 1999;Lam & Flores 2003;Moore, 1990;Chevanan et al, 2007a).Additionally, during the cooking process, the melted dough exhibits a pseudoplastic behavior and thus, a substantial decrease in the apparent viscosity of the dough, which is influenced by the temperature, moisture content and type of the ingredients and ultimately affects the extent of pressure release and expansion of the finished product (Rosentrater et al, 2005;Chevanan et al, 2007a). In general, the more moisture, the less expansion due to the lubricant effect of water and consequent decrease in apparent viscosity of the dough (Mjoun & Rosentrater, 2011); the higher the starch content, the greater the expansion due to starch gelatinization and elastic behaviour of the dough inside the barrel and consequent pressure rise at the die exit (Nielsen, 1976;Kokini et al, 1992;Case et al, 1992;Sokhey et al, 1994;Ibanoglu et al, 1996). Kim et al (1989) suggested that increasing the extent of expansion as a result of increase in barrel temperature could be related to more starch gelatinization and more excretion of super-heated steam.…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%
See 2 more Smart Citations
“…Expansion is mainly governed by the sudden decrease in pressure attheat the die section, which results in water phase transition and formation of air cells in the extrudates (Alves et al, 1999;Lam & Flores 2003;Moore, 1990;Chevanan et al, 2007a).Additionally, during the cooking process, the melted dough exhibits a pseudoplastic behavior and thus, a substantial decrease in the apparent viscosity of the dough, which is influenced by the temperature, moisture content and type of the ingredients and ultimately affects the extent of pressure release and expansion of the finished product (Rosentrater et al, 2005;Chevanan et al, 2007a). In general, the more moisture, the less expansion due to the lubricant effect of water and consequent decrease in apparent viscosity of the dough (Mjoun & Rosentrater, 2011); the higher the starch content, the greater the expansion due to starch gelatinization and elastic behaviour of the dough inside the barrel and consequent pressure rise at the die exit (Nielsen, 1976;Kokini et al, 1992;Case et al, 1992;Sokhey et al, 1994;Ibanoglu et al, 1996). Kim et al (1989) suggested that increasing the extent of expansion as a result of increase in barrel temperature could be related to more starch gelatinization and more excretion of super-heated steam.…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%
“…These observations for the increasing and decreasing values of ER and UD of the extrudates with 20% SPC inclusion confirm the direct and inverse relation of BD to UD and ER, respectively. Since the most floatable extrudates had the lowest BD and UD values, it is crucial to make a balance between the desired ER and BD values of the products (Mjoun & Rosentrater, 2011). 4.2.7 Water Absorption and Water Solubility Indices (WAI, WSI) Table 3 shows that inclusion of 20% SPC resulted in 17.5% increase in WAI compared to that of the control diet, while inclusion of 20% FSBM did not show a significant effect on WAI of the extrudates.…”
Section: Bulk Density (Bd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SME ranged between 209.3±4.72 to 236.6±11.06 as seen in Table 2, and it was inversely proportional to mass flow rate where Onwulata et al 2001 had mentioned that Specific mechanical energy integrates extrusion responses, such as net torque, screw speed and the product mass flow rates. Various studies proved that SME also decreased at high moisture content, (Mjoun, and Rosentrater 2011), however moisture being constant in the feed formulation only mass flow rate could impact the SME which was seen to decrease with increase in the mass flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, dynamic flow of the dough inside the die is drastically influenced by the temperature and the present water content. The high temperature and lubricant effect of water increase the molecules mobility and thus the melted dough exhibits pseudoplastic behavior leading to a substantial decrease in the apparent viscosity of the extruding dough which affects the extent of pressure release and ultimately reduces ER of the finished product (Chevanan et al, 2007a;Mjoun & Rosentrater, 2011;Rosentrater et al, 2005). While the higher the starch content results in a more expanded extrudates due to starch gelatinization and elastic characteristic of the dough inside the barrel and consequent pressure rise at the die exit (Ibanoglu et al, 1996;Kokini et al, 1992;Lin et al, 2000;Nielsen, 1976;Sokhey et al, 1994); the more incorporation of protein in the blend ingredients results in production of extrudates with more porous texture mainly because ofthe protein denaturation and plastic characteristic of the melted dough inside the extrusion www.ccsenet.org/jfr Journal of Food Research Vol.…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%